Cardiac Arrest Alters Regional Ubiquitin Levels in Association with the Blood–Brain Barrier Breakdown and Neuronal Damages in the Porcine Brain - Sharma H.S.; Patnaik R.; Sharma A.; Lafuente J.V.; Miclescu A.; Wiklund L. (My University, 2025)
The possibility that ubiquitin expression is altered in cardiac arrest-associated neuropathology was examined in a porcine model using immunohistochemical and biochemical methods. Our observations show that cardiac arrest induces progressive increase in ubiquitin expression in the cortex and hippocampus in a selective and specific manner as compared to corresponding control brains using enzyme-linked immunoassay technique (enzyme-linked immunosorbent assay (ELISA)). Furthermore, immunohistochemical studies showed ubiquitin expression in the neurons exhibiting immunoreaction in the cytoplasm and karyoplasm of distorted or damaged cells. Separate Nissl and ubiquitin staining showed damaged and distorted neurons and in the same cortical region ubiquitin expression indicating that ubiquitin expression after cardiac arrest represents dying neurons. The finding that methylene blue treatment markedly induced neuroprotection following identical cardiac arrest and reduced ubiquitin expression strengthens this view. Taken together, our observations are the first to show that cardiac arrest enhanced ubiquitin expression in the brain that is related to the magnitude of neuronal injury and the finding that methylene blue reduced ubiquitin expression points to its role in cell damage, not reported earlier. © 2015, Springer Science+Business Media New York.